Consumption of raw oysters: a risk factor for Vibrio parahaemolyticus infection - New, Chia Yeung (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2014)
Vibrio parahaemolyticus is recognized as a frequent causal agent of human gastroenteritis due to the consumption of raw, undercooked or mishandled seafood in many Asian countries. The number of V. parahaemolyticus cases reported is on the rise, and this becomes a concern to the Asian countries as seafood is favoured by Asians. This study aimed to detect and quantify V. parahaemolyticus in raw oysters and to determine the risk associated with the consumption of raw oysters. A total of 30 oyster samples were collected and analysed in this study. MPN-PCR and MPN-Plating methods were employed and carried out concurrently to determine the prevalence of V. parahaemolyticus in raw oysters. The results showed that the prevalence of total V. parahaemolyticus in oysters was 50.00% (15/30) where the MPN/g range was < 3 - > 11000 MPN/g for MPN-PCR method, and 40.00% (12/30) where the MPN/g range was < 3 - 4300 MPN/g for MPN-Plating method. MPN-PCR method was able to estimate the level of virulence (tdh+ and trh+) V. parahaemolyticus in the raw oysters where 10.00% (3/30) of samples were identified to be in a range of 3 - 30 MPN/g. A microbial risk assessment was conducted based on the enumeration data obtained from MPN-PCR method using @risk. The probability of illness annually was 1.76 × 10-6 with a prediction of 31 cases to occur with respect to the exposed Malaysian population, while the rate per 100,000 people was estimated to be at 0.104. In addition, the antibiogram of V. parahaemolyticus was determined using Kirby Bauer Disk Diffusion Test and the results indicated that the isolates were highly resistant towards Bacitracin (100.00%), Vancomycin (100.00%) and were least resistant to Chloramphenicol (8.70%). The MAR index of the isolates ranged from 0.17 to 0.50. In accordance with the results from this study, the consumption of raw oysters is a risk factor for V. parahaemolyticus infection and proactive actions should be taken to reduce the risk of the pathogen in order to improve public health.